Role of personal values and personality traits on intention to recommend a destination - Japutra, A. (2021)
In this study, the researchers explore the antecedents of tourists’ intention to recommend a destination using an extended Theory of Planned Behavior (TPB). Two personal values (i.e., prosocial and maturity) and two personality traits (i.e., extraversion and agreeableness), which are rarely studied but important elements for marketers to better understand the market (e.g., segment the market), are examined. To test the extended model of TPB, a survey (n=312) was conducted with tourists in Portugal. The researchers find support for the hypothesis that tourists with higher prosocial values, maturity values, and extraversion personality traits are more likely to have a favorable attitude toward a destination and a tendency to recommend the destination. Theoretical and managerial implications are discussed.